Pengaruh Pemanfaatan Limbah Kawat Bendrat Sebagai Pengganti Sebagian Agregat Halus Terhadap Kuat Tekan Beton - Lestari, Galindra Sekar; Kadarningsih, Rahmani (Lambung Mangkurat University Press, 2025)
Every year, millions of tons of construction waste are produced, including wire mesh that is often left unused from the cutting and installation processes. Wire mesh, which serves as a reinforcement for concrete, frequently ends up as waste. With the increasing amount of construction waste, this research proposes the utilization of wire mesh as a partial substitute for fine aggregate in concrete mixtures with variations of 0%, 5%, 7.5%, and 10% by weight of sand, targeting compressive strengths of 21 MPa and 25 MPa. Additionally, 8% fly ash and 0.5% superplasticizer by weight of cement were used. Test specimens were cylindrical, with a diameter of 15 cm and a height of 30 cm, and were tested for compressive strength after 28 days. The results showed an increase in compressive strength of 36% and 9% for concrete grades of 21 MPa and 25 MPa, with the optimum percentage of wire mesh addition being 5%, which resulted in compressive strengths of 33.20 MPa and 31.73 MPa, respectively. However, the compressive strength significantly decreased at the 10% wire mesh variation, with average compressive strengths for the target grades of 21 MPa and 25 MPa being 23.67 MPa and 16.43 MPa, respectively.